Task Analysis in Human-Computer Interaction: A Comparison between Four Task Analysis Techniques - Samia Abdalhamid; Tahani Almabruk; Haduth, Laila; Asma Abd Aljalil; Rafig Almaghairbe (AlQalam Journal of Medical and Applied Sciences, 2023)
Task analysis is an integral part of human-computer interaction, as it permits the client to comprehend, complete, and benefit from the utilization of an interaction system. Task analysis methodologies differ based on the selected approach and the motivation behind its use. The present study aims to compare several task analysis methodologies (i.e. hierarchical task analysis, cognitive task analysis, GOMS task analysis, and emotion task analysis), initially outlining their commonalities and distinctions in structure and usability. After that, it will go into each technique's benefits and drawbacks and how well-suited it is for different jobs. The main results that have been obtained by this research are: the HTA technique is an appropriate selection when the analysis seeks to explore the connections and interdependencies among different components of the task, whereas CTA is appropriate for the analysis that necessitates a technique with an undefined structure comprising of interviews. If the analysis system seeks to identify a cognitive process with a clearly defined structure, the GOMs technique can be a superb option. Lastly, when the task analysis aims to comprehend the emotional aspects of task performance, the ETA serves as an effective instrument to employ. In terms of usability, HTA is widely utilized in the fields of task assistance design and error prediction. CTA proves to be beneficial for tasks that demand sophisticated cognitive functions, GOMS is typically employed in the creation of training tools, the design of assist frameworks, and the documentation for clients, and ETA examines how users' psychological or emotional states influence their responses to tasks as they complete them. It is advised that readers go over this comparison paper in order to obtain a better knowledge of how to select the precise strategy that can aid in finishing an assignment. تحليل المهمة هو جزء أساسي من تفاعل الإنسان مع الحاسوب، حيث يسمح للعميل بفهم، وإكمال، والاستفادة من استخدام نظام التفاعل. تختلف منهجيات تحليل المهمة بناءً على النهج المختار والدافع وراء استخدامها. تهدف الدراسة الحالية الي مقارنة عدة منهجيات لتحليل المهمة (مثل تحليل المهمة الهرمي HTAوتحليل المهمة الذهني CTA وتحليل المهمة GOMS وتحليل المهمة العاطفي ETA)، حيث يتم في البداية توضيح توجهاتها واختلافاتها في الهيكل والاستخدام. بعد ذلك ستتناول الدراسة فوائد وعيوب كل تقنية ومدي وملاءمتها لوظائف مختلفة. النتائج الرئيسية التي تم الحصول عليها من هذا البحث هي كالتالي: تقنية HTA تعتبر اختيار مناسب عندما يسعي التحليل لاستكشاف وجود الروابط من عدمها خلال عدة مكونات للمهمة، في حين CTA هو الاختيار الأفضل لتحليل هيكل غير محدد يتضمن اجراء مقابلات. إذا كان النظام يسعي الي تحليل مهمة ادراكية او ذهنية ذات بنية واضحة فان GOMS يمكن ان يكون التقنية الأكثر ملائمة. أخيرا عندما يكون هدف تحليل المهمة هو فهم الجوانب العاطفية والنفسية لإداء المهمة فان ETA يعد الأكثر فاعلية في مثل هذه الحالات. من حيث الاستخدام، تقنية HTA تستخدم على نطاق واسع في مجالات تصميم المهمة وتوقع الأخطاء. في حين تم اثبات نجاح تقنية CTA في انجاز المهام التي تتطلب وظائف ادراكية معقدة بينما تميزت تقنية GOMs بقدرتها على انشاء أدوات التدريب وتصميم أطُر المساعدة ووثائق العملاء. تقنية ETA تستخدم لدراسة حالة المستخدم النفسية والعاطفية عند استجابته للمهام وادائها. يُنصح القراء والبحاث بمراجعة ورقة المقارنة هذه للحصول على معرفة أفضل حول كيفية اختيار الاستراتيجية الدقيقة التي يمكن أن تساعد في اكمال المهمة.